From active plasmonic devices to plasmonic molecular electronics. Issue 4 (23rd January 2019) - Lacroix, Jean‐Christophe; van Nguyen, Quynh; Ai, Yong; van Nguyen, Quyen; Martin, Pascal; Lacaze, Pierre‐Camille
Abstract: This work is mainly focused on studies combining plasmonic nanostructures and π‐conjugated systems. It describes active molecular plasmonic devices in which π‐conjugated molecules and polymers, grafted on gold nanoparticles, are used to tune the plasmonic properties of metal nanostructures. It also explores two emerging research fields, i.e. plasmonic electrochemistry and plasmonic molecular electronics. In the former, electrochemical reactions are controlled and triggered by plasmons which yield various light‐induced electrochemical reactions at the nanoscale. In the latter, one combines molecular plasmonics and molecular electronics in plasmonic molecular devices. © 2018 Society of Chemical Industry Abstract : This work is focused on studies combining plasmonic nanostructures and π‐conjugated systems. It describes active molecular plasmonic devices and explores plasmonic electrochemistry and plasmonic molecular electronics.